2018
DOI: 10.1007/s13555-018-0229-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aging Properties of Conditioned Media of Epidermal Progenitor Cells Derived from Mesenchymal Stem Cells

Abstract: IntroductionReduced number and activities of epidermal stem cells are related to the features of photoaged skin. It was reported that conditioned media from various stem cell cultures are capable of improving the signs of cutaneous aging. This work was performed to establish epidermal progenitor cells derived from mesenchymal stem cells, and to evaluate the anti-aging efficacy of its conditioned media.MethodsEpidermal progenitor cell culture was established by differentiation from mesenchymal stem cells, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…Previously, we reported that the topical application of a conditioned media of epidermal progenitor cells derived from mesenchymal stem cells, which contained high levels of nidogen-1, significantly improved various skin aging parameters, such as wrinkle and skin texture, which is consistent with current result [34] In this study, the potential application of epidermal protein expression-modulating ingredients as anti-aging cosmeceuticals was investigated. Three peptide derivatives with stimulatory activities on collagen XVII, laminin and nidogen in vitro, were used in a mixed form, and their anti-aging activities were examined using ex vivo and clinical studies.…”
Section: Discussionsupporting
confidence: 88%
“…Previously, we reported that the topical application of a conditioned media of epidermal progenitor cells derived from mesenchymal stem cells, which contained high levels of nidogen-1, significantly improved various skin aging parameters, such as wrinkle and skin texture, which is consistent with current result [34] In this study, the potential application of epidermal protein expression-modulating ingredients as anti-aging cosmeceuticals was investigated. Three peptide derivatives with stimulatory activities on collagen XVII, laminin and nidogen in vitro, were used in a mixed form, and their anti-aging activities were examined using ex vivo and clinical studies.…”
Section: Discussionsupporting
confidence: 88%
“…In order to validate secretome profiling of MSC derived CM, we initially performed proteomic profiling of CM using human specific ELISA kits and bead based multiplex method and the data of the same is already reported [10]. It is in corroboration with the cytokines/growth factors identified in the CM derived from MSC cultures published by other researchers [13,[16][17][18][19]. Since the aim of the present study was to evaluate anti-aging potential of human MSC derived CM formulation, we specifically selected two of the widely studied growth factors VEGF and TGF-β which are important for maintaining healthy skin.…”
Section: Pre-formulation Studies Of Concentrated CMsupporting
confidence: 59%
“…Liu et al, showed that umbilical cord mesenchymal stem cells CM protects against photo aging induced by UVA and UVB radiation and is a promising candidate for skin anti-photo aging treatments [12]. Sohn et al, demonstrated the anti-aging properties of CM of epidermal progenitor cells derived from mesenchymal stem cells [13]. Moreover, CM derived from various stem cells have been used in anti-aging formulations and hair growth promoting cosmetic formulations [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the pathology, stem‐like skin‐derived cells help fibroblasts to either secrete wound healing related proteins or reduce ECM deposition 26 . Moreover, dermal fibroblasts have been used clinically for the treatment of various non‐healing wounds and genetic diseases 27‐29 . In our study, we investigated the effect of the secretome (secreted proteome/metabolome) produced by both stem‐like skin‐derived cells and fibroblasts to counter the damage of sunlight radiation.…”
Section: Discussionmentioning
confidence: 99%